SYSTEMATIC ART EDUCATION MODEL FOR GRADES 5–7 IN MODERN SCHOOLS - Boboqulov Javohir Hamzayevich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article presents a model for systematic art education designed for students in grades 5–7 within contemporary school settings. The study emphasizes the importance of structured, progressive instruction that integrates foundational skills, creative development, and aesthetic understanding. The proposed model combines traditional art techniques with innovative pedagogical strategies, including project-based learning, digital visualization, and tiered lesson planning, to enhance students’ engagement and skill acquisition. By providing a clear framework for lesson organization, the model supports consistent development of technical proficiency, artistic creativity, and visual literacy. Additionally, it fosters critical thinking, problem-solving, and cultural awareness, preparing students to interpret and express the visual world confidently and meaningfully.